Antioxidative enzymes and increased oxidative stress in depressive women - Kodydková, Jana; Vávrová, Lucie; Zeman, Miroslav; Jirák, Roman; Macásek, Jaroslav; Stanková, Barbora; Tvrzická, Eva; Zák, Ales (Clinical biochemistry, 2009)
OBJECTIVES: To investigate the activities of the main antioxidative enzymes and oxidative stress in women with depressive disorder (DD). METHODS: In 35 drug-naive women with DD and 35 age matched healthy women enzymes superoxide dismutase (CuZnSOD), catalase (CAT), glutathione peroxidase (GPX1), glutathione reductase (GR) and paraoxonase (PON1), concentrations of conjugated dienes (CD), reduced glutathione (GSH) and anthropometric and clinical data were investigated. RESULTS: Women with DD were found to have decreased activities of GPX1 (p<0.05), decreased concentrations of GSH (p<0.05), and increased activities of GR (p<0.05), CuZnSOD (p<0.001), and concentrations of CD (p<0.05). Activity of GPX1 was positively correlated with concentration of GSH (p<0.05). Concentrations of CD were positively correlated with TG (p<0.01). CONCLUSION: Our set of depressive women was characterized by changes indicating an increased oxidative stress, as well as by certain features of metabolic syndrome.
Keywords: oxidační stres; Glutathione Reductase; Enzymes; glutathionperoxidasa; Alkadienes; enzymy; Aged; senioři; triglyceridy; depresivní poruchy; Catalase; oxidace-redukce; glutathion; Aryldialkylphosphatase; lidé; ženské pohlaví; Humans; katalasa; glutathionreduktasa; alkadieny; spektrofotometrie; Depressive Disorder; Glutathione; Triglycerides; aryldialkylfosfatasa; Spectrophotometry; Superoxide Dismutase; Glutathione Peroxidase; Oxidation-Reduction; Female; Oxidative Stress; lidé středního věku; superoxiddismutasa; Middle Aged